(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
this article provides information on the reforms in the field of the public administration system of the Bukhara Khanate during the reign of the Shaybanids, the formation, centralization, central and local administration of the Bukhara Khanate, as well as the family administration of the Shaybanid dynasty in Movarunnahr, administrative and clerical work on individual estates under them is analyzed.